Patient-Centric Care for Parkinson's Disease: From Hospital to the Community - Aye, Yin Minn; Liew, Sylvia; Neo, Shermyn Xiumin; Li, Wei; Ng, Hwee-Lan; Chua, Shu-Ting; Zhou, Wen-Tao; Au, Wing-Lok; Tan, Eng-King; Tay, Kay-Yaw; Tan, Louis Chew-Seng; Xu, Zheyu (Frontiers in Neurology, 2020)
Parkinson’s Disease (PD) is a chronic neurodegenerative disease with complex motor and non- symptoms often leading to significant caregiver burden. An integrated, multidisciplinary care setup involving different healthcare professionals is the mainstay in the holistic management of PD. Many challenges in delivering multidisciplinary team (MDT) care exist such as insufficient expertise amongst different health care professionals, poor interdisciplinary collaboration and communication. The need to attend different clinics, incurring additional travelling and waiting time for allied health therapies can also make MDT care more burdensome. By shifting MDT care to local community settings and into patients’ homes, patient-centred care can be achieved. In Singapore, the National Neuroscience Institute created the Community Care Partners Programme in 2007 to bring the allied MDT team to the community and nurse-led Integrated Community Care Programme for Parkinson’s Disease in 2012 to provide care in community and at patient’s home. However, attaining MDT care in community setting is difficult to achieve where there is a shortage of PD trained professionals. As such interdisciplinary and transdisciplinary management would be other best practice options to deliver patient-centric care in PD. Telemedicine could be another viable option to bring the MDT closer to the patient.